Vitamin E as a protective factor against neurological diseases (Research, Society and Development, 2022)
Despite being an essential nutrient for humans, unlike most nutrients, the vitamin E does not have a specific role in metabolic functions, but the deficiency can cause a number of symptoms that include progressive neurological disorder, spinocerebellar ataxia, and death of peripheral nerves, specifically sensory neurons. This present investigation is a systematic review that aimed to elucidate the influence and role of vitamin E in the preservation of human neurological health, as well as probable neuroprotective mechanisms related to nutritional deficiency, increment of vitamin E in the diet and improvement of the quality of life in patients with neurological disorders. For the selection of articles, were selected the databases Scientific Electronic Library Online (SciELO), Virtual Health Library Portal (BVS) and Elsevier, in addition to articles published in the last five years. After analyzing the articles included in this review, the results of the studies showed that vitamin E is associated with improvement and prevention of several neurological disorders, such as Parkinson's disease, Alzheimer's disease, effects on synaptic plasticity and cognitive function in the hippocampus after traumatic brain injury, cognitive deficit in hypothyroidism and also had a protective role in neural tube development in mouse fetuses.